2021
DOI: 10.1038/s41598-021-88652-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the major QTLs for biochemical variation of sulforaphane in broccoli florets using a DH population

Abstract: Glucoraphanin is a major secondary metabolite found inBrassicaceaevegetables, especially broccoli, and its degradation product sulforaphane plays an essential role in anticancer. The fine mapping of sulforaphane metabolism quantitative trait loci (QTLs) in broccoli florets is necessary for future marker-assisted selection strategies. In this study, we utilized a doubled haploid population consisting of 176 lines derived from two inbred lines (86,101 and 90,196) with significant differences in sulforaphane cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…obviously observed on the cytoplasm and nucleus under laser confocal microscopy, as shown in Figure 7. Therefore, this result indicated that the genes Bol031350, which is related to glucosinolate metabolism, and CRa, which is related to resistance to clubroot, were both expressed in the cytoplasm and nucleus, which was consistent with previous studies (Li et al, 2021a;Abdel-Ghany et al, 2005;Bai et al, 2014).…”
Section: Subcellular Localizationsupporting
confidence: 91%
“…obviously observed on the cytoplasm and nucleus under laser confocal microscopy, as shown in Figure 7. Therefore, this result indicated that the genes Bol031350, which is related to glucosinolate metabolism, and CRa, which is related to resistance to clubroot, were both expressed in the cytoplasm and nucleus, which was consistent with previous studies (Li et al, 2021a;Abdel-Ghany et al, 2005;Bai et al, 2014).…”
Section: Subcellular Localizationsupporting
confidence: 91%
“…Thirdly, the side chain is modified in a process controlled by a flavin-containing monooxygenase (FMOGS-OX), which mediates the formation of different glucosinolate structures [ 18 ]. In addition, AOP3 (2-oxoglutarate-dependent dioxygenases) can catalyze the conversion of glucoraphanin to hydroxyalkyl glucosinolate, whereas MYR (myrosinase) can catalyze the degradation of glucoraphanin to sulforaphane in all Brassicaceae [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the research on important gene mining and their regulatory mechanism of B. oleracea crops has entered a period of rapid development. A series of genetic loci or genes controlling plant growth, resistance to biotic and abiotic stresses, quality composition and fertility, etc., have been excavated ( Li et al., 2021 ; Shaw et al., 2021 ; Zhang et al., 2021 ; Han et al., 2021 ; Ren et al., 2022 ; Alemán et al., 2022 ). Therefore, the effective transformation method established in this study will greatly accelerate the functional validation and regulatory mechanism study of the target genes controlling important agronomic traits of B. oleracea crops and promote rapid gene pyramiding to develop excellent target materials.…”
Section: Discussionmentioning
confidence: 99%